Evaluation of onboard radiometric system for remote sensing detection of heightened radioactivity of soil - Kolotkov, G. A. (Atomic energy)
A remote sensing method of monitoring heightened soil radioactivity using an onboard radiometer that records indirect effects in the environment is examined. The gamma-spectrometric field surveying was used to determine the soil content of uranium, thorium, and potassium in southeastern Tomsk. Heightened uranium content was found in soil samples from Kuzovlevo village, Nadezhda village, TGOK Il'menit and high thorium in samples from Svetloe village, and Aleksandrrov section of TGOK Ilmenit, Kuskovo City, and Zorkal'tsevo Village. The energy spectra and average characteristics of the beta-decay electrons of potassium-40 in soil were obtained.